Wzrost szczepów lipy drobnolistnej (Tilia cordata Mill.) na plantacji nasiennej w Nadleśnictwie Susz - Ludwikowska, Agata; Kowalkowski, Wojciech; Tarasiuk, Stefan (Leśne Prace Badawcze, 2011)
The Susz Forest District contains one of two Tilia cordata seed orchards established in Poland in 1985-1986. Most of the clones in this seed orchard originate from overstorey trees from selected seed stands in the Młynary Forest District. Although all clones were of the same age and grown under similar conditions, variation in their average height growth was high and ranged from 4.20 m (clone no. 2855) to 8.50 m (clone no. 3522), while variation in the average DBH ranged from 4.50 cm (clone no. 3299) to 19.50 cm (clone no. 3522). There were large morphological differences between the seeds of different clones, both in terms of their dimensions and characteristics such as colour and hairy shoots. Overall mortality of all the clones planted in the seed orchard was 20 %. Seed production in the seed orchard steadily decreased since 1997. In 2005, the harvest of seeds was stopped because most seeds turned out to be empty. Soil acidity in the seed orchard was too high (pH